Origin of Middle-Upper Cambrian dolomites in eastern Laurentia: A case study from Belle Isle strait, western Newfoundland. (March 2021) - Shembilu, Noel; Azmy, Karem; Blamey, Nigel
Abstract: The Middle and Upper Cambrian Port au Port Group of western Newfoundland consists mainly of mixed carbonates and siliciclastics and is composed of the March Point, Petit Jardin, and Berry Head formations. Samples were collected from the core NF-02 that spans the uppermost Hawke Bay (40 m), the March Point ( 83 m thick) and the lowermost Petit Jardin ( 47 m). Petrographic examination of carbonates of the March Point and Petit Jardin carbonates reveals three generations of dolomite: (i) micritic to near-micritic (D1, 4 μm −35 μm) fabric-retentive dolomite, (ii) coarse crystalline sucrosic (D2, 60 μm−150 μm) fabric-destructive dolomite (sub-to euhedral zoned rhombs with clear rim and cloudy core), and (iii) coarse anhedral (D3, >0.5 mm) fracture-filling saddle dolomite. The microthermometric measurements of primary two-phased fluid inclusions retained in D2, and D3 samples yielded homogenization temperatures (T h ) showing a general increase with burial. The mean values of T h and salinity are 89.1 ± 6.4 °C vs 21.2 ± 2.2 eq. wt% NaCl, and 110 ± 8.2 °C vs 21.1 ± 4.7 eq. wt% NaCl, respectively. The investigated dolomites show a decrease of Sr from D1 (102 ± 49 ppm) to D3 (47 ± 15 ppm) which reflects the influence of progressive burial. The mean δ 18 O values decrease from D1 (−6.3 ± −1.1‰ VPDB), to D3 (−9.7 ± 1.7‰ VPDB) where D2 (−7.6 ± 1.2‰ VPDB) is in the middle. The estimated δ 18 O values of the D1 parent fluid (−5 to −10‰ VSMOW) are bracketed by those suggested for the Middle Cambrian meteoric and seawaters. The fluid-inclusion gas analyses provided CO2 /CH4 and N2 /Ar ratios coherent with the conclusions from the petrographic examination and geochemical compositions. Highlights: Origin of dolomites reflected by their REE geochemistry. Dolomite D1 was formed under near-surface condition and fluids were possibly mixed sea and meteoric waters. Fluid inclusion gas analysis establishes the oxidation state and distinguish the origin of source fluids. Controls of dolomitization on porosity distribution patterns. The δ 13 C values of D1 fall within the documented range of the best-preserved Cambrian marine carbonates.